Our current understanding of the toxicity of altered mito-ribosomal fidelity during mitochondrial protein synthesis: What can it tell us about human disease? - Vila-Sanjurjo, Antón; Mallo, Natalia; Atkins, John F.; Elson, Joanna L.; Smith, Paul M. (Frontiers in Physiology, 2023)
Altered mito-ribosomal fidelity is an important and insufficiently understood causative agent of mitochondrial dysfunction. Its pathogenic effects are particularly well-known in the case of mitochondrially induced deafness, due to the existence of the, so called, ototoxic variants at positions 847C (m.1494C) and 908A (m.1555A) of 12S mitochondrial (mt-) rRNA. It was shown long ago that the pathogenicity of these variants could remain dormant until an external stimulus triggered their pathogenicity. Yet, the link from the fidelity defect at the mito-ribosomal level to its phenotypic manifestation remained obscure. Recent work with fidelity-impaired mito-ribosomes carrying error-prone and hyper-accurate mutations in mito-ribosomal proteins have started to reveal the complexities of the phenotypic manifestation of mito-ribosomal fidelity defects, leading to a new understanding of mtDNA disease. While much needs to be done to arrive to a clear picture of how defects at the level of mito-ribosomal translation eventually result in the complex patterns of disease observed in patients, the current evidence indicates that altered mito-ribosome function, even at very low levels, may become highly pathogenic. The aims of this review are three-fold. First, we compare the molecular details associated to mito-ribosomal fidelity to those of general ribosomal fidelity. Second, we gather information on the cellular and organismal phenotypes associated to defective translational fidelity in order to provide the necessary grounds for an understanding of the phenotypic manifestation of defective mito-ribosomal fidelity. Finally, the results of recent experiments directly tackling mito-ribosomal fidelity are reviewed and future paths of investigation are discussed.